Amplifying Student Voice In Integrity Zone-Based University Complaint Systems - Ariatna; Rita Suswati; Juli Rachmadani Hasibuan; Yeni Erlita (Journal of Innovation Research and Knowledge, 2026)
The implementation of Integrity Zone initiatives in higher education emphasizes transparency, accountability, and service quality as key principles of good governance. However, the standardization of student complaint-handling systems within the Integrity Zone framework remains underexplored. This study investigates students’ needs for a standardized complaint-handling system in the Department of English Language and Literature, Faculty of Languages and Arts, Universitas Negeri Medan, Indonesia. Using a descriptive needs analysis approach as the preliminary stage of an ADDIE-based Research and Development (R&D) project, data were collected from 135 students, consisting of 81 English Education students and 54 English Literature students. The instrument included ten Likert-scale items and four open-ended questions. Quantitative findings revealed a substantial gap between existing complaint-handling practices and students’ expectations. The overall perception of the current system was moderate (M = 2.62, SD = 0.94). Low ratings were found for Information Transparency and Accessibility (M = 2.22, SD = 1.07), Procedural Certainty and Complaint Categorization (M = 2.29, SD = 1.00), and Complaint Resolution Effectiveness (M = 2.26, SD = 0.95). The lowest score was recorded for Safety and Procedural Protection (M = 1.97, SD = 0.98), indicating concerns regarding confidentiality and fear of academic retaliation. Conversely, students expressed very strong support for a standardized complaint-handling system (M = 4.38, SD = 0.70). Qualitative findings identified four key needs: anonymity protection, complaint tracking, procedural safeguards, and a web-based reporting platform. The findings provide an empirical foundation for developing an Integrity Zone-based SOP and digital complaint-management system to strengthen accountability, institutional trust, and service quality in higher education